Understanding The Concept of Halal Lifestyle to Culinary Among The People of Pontianak - Saragih, Eka Junila (TAWAZUN: Journal of Sharia Economic Law, 2024)
This study aims to examine Pontianak's understanding of the concept of halal lifestyle. As is known at this time the government strives for all sectors such as halal tourism, halal lodging, halal medicines, food and halal drinks and so on have halal certification. In the city of Pontianak itself is famous for its culinary tourism. Starting from Muslim traders to non-Muslims. However, here there are several non-Muslim traders who put a halal label on their wares. These businesses sell a variety of food and beverages. The author sees that most people who are Muslim buy these foods or drinks, while Muslim traders also sell the same types of food and drinks. They only see the halal label listed without understanding the meaning of halal itself. They revealed that the most important thing is that they have a halal label and the food being sold is halal food. It is very clear that people do not understand the concept of halal itself. Even though good and healthy food is halal food and thayyib. Not all foods labeled halal products are halal, and vice versa. Therefore as Muslims they must pay attention to the cleanliness of the food and halalness of these foods. The author is of the opinion that food whose law is unclear is a doubtful matter. Syubhat is ambiguity or obscurity, so that something cannot be known clearly as halal. So that Allah swt commands humans to leave doubtful matters